Automated car parking system - Mubashirin, Maksura; Mahmud, Srabosti (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.